2011
DOI: 10.1177/0091270010379410
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Tolerability of Ascending Doses of Sublingual Fentanyl, With and Without Naltrexone, in Japanese Subjects

Abstract: This open-label, nonrandomized study assessed single and repeat ascending doses of a new sublingual fentanyl (SLF) formulation in 48 healthy Japanese opiate-naïve subjects (47 completed). Subjects received single-dose SLF 100, 200, 400, or 800 µg followed by 13 doses 6 hourly, at their dose level. Subjects taking repeat-dose 400 and 800 µg were pretreated with naltrexone in order to block opiate-receptor-mediated effects on respiration, monitored by pulse oximetry and transcutaneous pco(2). Sublingual fentanyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In the current study, fentanyl induced respiratory depression at subcutaneous cumulative fentanyl doses above 12.5-25 mg/kg in sKLH-treated and naive rats. In humans, sublingual doses of 800 mg (11 mg/kg in a 70-kg human) caused respiratory depression after 2 hours in all 12 subjects (Lister et al, 2011). In another study (Dahan et al, 2005), apnea was reported in human subjects at an intravenous fentanyl dose as low as 2.9 mg/kg, and that prolonged apnea occurred at 7.1 mg/kg, leading the investigators to halt using this dose for the remainder of the study.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, fentanyl induced respiratory depression at subcutaneous cumulative fentanyl doses above 12.5-25 mg/kg in sKLH-treated and naive rats. In humans, sublingual doses of 800 mg (11 mg/kg in a 70-kg human) caused respiratory depression after 2 hours in all 12 subjects (Lister et al, 2011). In another study (Dahan et al, 2005), apnea was reported in human subjects at an intravenous fentanyl dose as low as 2.9 mg/kg, and that prolonged apnea occurred at 7.1 mg/kg, leading the investigators to halt using this dose for the remainder of the study.…”
Section: Discussionmentioning
confidence: 99%
“…[79] Subjects received SLF 100, 200, 400 or 800 μg every 6 hours for a total of 14 doses. Subjects administered repeated doses of SLF 400 μg or 800 μg also received naltrexone to prevent opioid-mediated respiratory depression.…”
Section: Current Treatments For Btpmentioning
confidence: 99%
“…The pharmacokinetics of the sublingual fentanyl orally disintegrating tablet have been investigated in normal volunteers, 7,8 and cancer patients. 9 However, there appears to be no data on the pharmacokinetics of sublingual fentanyl orally disintegrating tablets, or indeed other oral transmucosal opioids, in patients with salivary gland hypofunction.…”
Section: Introductionmentioning
confidence: 99%